Social marginalization risk and its negative association with socialising preferences in Japanese gamers - Brian Confessor; Monica Perusquia-Hernandez; Kongmeng Liew; Hideaki Uchiyama; Naoya Isoyama; Kiyoshi Kiyokawa (PLoS ONE, 2026)
For people with a high risk of social withdrawal, such as Japanese “hikikomori” or NEET, socialising with others can be demanding. For some, however, an alternative to direct real-world socialisation comes in the form of videogames. Past research suggests that videogames could help by providing opportunities for virtual social interaction and relational wellbeing management. But would those with a high risk of social marginalization also withdraw from social interaction in games? Past research entertains both possibilities: individuals may avoid socialising in-game as they do offline, but the anonymity of online gaming could afford safer opportunities for social interaction. To better understand the potential of game-based interventions for audiences at high risk of social withdrawal, we investigated gaming preferences of Japanese players (N = 587) with varying levels of NEET-Hikikomori risk. We hypothesized that higher withdrawal risk, measured by the NHR Scale, could either positively or negatively relate to player socialisation and cooperation, as measured by the HEXAD and Game Traits scales. After accounting for age, gender and extraversion, results showed that higher NHR score was associated with lower HEXAD Socialiser, lower HEXAD Philanthropist and lower Game Traits Social orientation scores, suggesting a negative association between NEET-Hikikomori risk and player traits related to socialisation. Furthermore, exploratory analysis showed that a higher NHR score was associated with lower scores in HEXAD Achiever and Game Traits Challenges orientation, suggesting NEET-Hikikomori risk has a negative correlation with challenges and achievement-related gameplay. These findings demonstrate how understanding specific gamer personality types is essential for designing experiences that can act as bridges towards more socialisation, while avoiding the risk of worsening players’ conditions through misaligned design.